Possibilities of Using Macrolepiota procera in the Production of Prohealth Food and in Medicine - Iwona Adamska; Grzegorz Tokarczyk (International Journal of Food Science)
Parasol mushroom (Macrolepiota procera) is a fungus that is often included in the menu of people looking for replacements for meat products and at the same time appreciating mushrooms. Its fruiting bodies are known for their delicate flavor and aroma. The aim of the publication was to analyze the latest information (mainly from 2015 to 2021) on the chemical composition of the M. procera fruiting bodies and their antioxidant properties. The data on other health-promoting properties and the possibilities of using these mushrooms in medicine were also compiled and summarized, taking into account their antibacterial, antioxidant, anti-inflammatory, regulatory, antidepressant, and anticancer effects. Moreover, the influence of various forms of processing and conservation of raw mushroom on its health-promoting properties was discussed. The possibilities of controlling the quality of both the raw material and the prepared dishes were also discussed. Such an opportunity is offered by the possibility of modifying the growing conditions, in particular, the appropriate selection of the substrate for mushroom cultivation and the deliberate enrichment of its composition with the selected substances, which will then be incorporated into the fungus organism.